Physiology is a hidden dimension of diversity in the radiation of woodland salamanders - Nathalie M. Alomar; Henry Camarillo; Edward D. Burress; Julia Laterza-Barbosa; Meaghan R. Gade; Saúl F. Domínguez-Guerrero; Isabela Hernández-Rodríguez; Laura R. V. Alencar; Brooke L. Bodensteiner; Isabella J. Burger; Eric A. Riddell; Martha M. Muñoz (Proceedings of the National Academy of Sciences, 2026)
Morphological evolution can be explosive, producing visually spectacular adaptive radiations like Caribbean anoles, Malagasy vangas, and African Rift Lake cichlids. Yet morphological stasis, the long-term retention of a conserved body plan, is often observed across evolutionary radiations. Woodland salamanders ( Plethodon ) are a classic example of such “nonadaptive” radiation, characterized by prolific speciation alongside morphological stasis (i.e., limited morphological divergence), often attributed to phylogenetic conservatism in their climatic and microhabitat niches. However, the multidimensional nature of phenotypes and the niche means that adaptive evolution in less apparent traits can occur even when morphology appears static. We investigated whether woodland salamanders exhibit adaptive divergence in a less conspicuous phenotypic axis—specifically, physiology—and compared patterns and rates of trait evolution to those of morphological traits. We found that most physiological traits are associated with climatic variation and exhibit elevated rates of evolution, high trait disparity, and more frequent shifts in adaptive optima than morphological traits. In particular, skin resistance to water loss, metabolic rate, and cold tolerance exhibit evolutionary signatures of adaptive radiation. Notably, morphology is not entirely static: Some traits show climatic associations, several exhibit localized shifts, and evolutionary rates exceed those of slower evolving physiological traits, such as heat tolerance. Biological systems, as evidenced by woodland salamanders, are not exclusively “conserved” or “labile” in their evolution, and this system illustrates how the same features that limit morphological divergence may also facilitate physiological evolution. Woodland salamanders exemplify how adaptive radiation can proceed despite outward similarity.